Challenges Encountered by Indigenous Children in Self-Learning Module during New Normal Education - Bench G. Fabros; Janine T. Ancheta; Audley Jan R. Balanay; Mharey D. Bellen; Alexandria Shane S. Cuario (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The impoverished and indigenous peoples are the most seriously affected groups in the Philippines' abrupt shift in curriculum due to the risk of the COVID-19 outbreak who reside in rural areas where the provision of basic services has been challenging. This study aims to determine the challenges faced by indigenous children in the self-learning module. Using a researcher-made validated semi-structured interview, the study implemented a qualitative narrative research method design wherein responses were gathered from participants' interviews, experiences, and challenges encountered in the self-learning module. The participants of the study were two (2) kindergarten parents and one (1) grade 3 parent from Sitio Poquiz Maasin, San Clemente, Tarlac, Philippines. As an outcome, the pandemic affects the learning of indigenous children. Loss of motivation showed that learners were becoming lazy when answering and completing their modules. The learners also showed they had challenges in concentrating, which has an effect on the learning and teaching experiences. Because of their parents' limited education, challenges in understanding the module were noted, and unclear instructions in the modules made it challenging for students to answer. Despite these challenges, the researchers lay out some alternative ways and interventions that can be utilized to cope up with the new normal education.